The effects of male out-migration on household food security in rural Nepal. - Janet_Kim, Jeeyon; Stites, Elizabeth; Webb, Patrick; Constas, Mark; Maxwell, Daniel. (Tufts University. Tisch Library., 2019)
In Nepal, international migration is a highly gendered phenomenon. Compared to global figures, where women make up about half of the world's migrant population, 90% of Nepalese migrants are men. Many of these men migrate alone to earn wages abroad while their families stay behind. This level of male out-migration in Nepal occurs in a context characterized by widespread food insecurity. This paper examines the effects of male out-migration on household food security, especially on the women who stay behind, in the mountains of Far West Nepal.